2003
DOI: 10.1007/bf02850201
|View full text |Cite
|
Sign up to set email alerts
|

Possible impact of nitric oxide on the antihypertensive effect of captopril and zaprinast

Abstract: The interaction between the renin-angiotensin system and nitric oxide (NO) is undeniable, but its nature is not fully known. This study investigated the contribution of NO to the acute hypotensive effect of captopril in conscious normotensive rats and the effect on blood pressure of dual administration of captopril and the phosphodiesterase-5 inhibitor zaprinast. In two separate experiments, rats were pretreated with the NO inhibitor L-arginine methyl ester (L-NAME) and with the NO enhancer zaprinast. Pretreat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 12 publications
0
1
0
Order By: Relevance
“…The medication was dosed based on previous work that suggested that beneficial effects on regional blood flow and cyclic mononucleotide levels without a significant reduction in mean arterial pressure could be achieved at 10 to 20 mg/kg doses. [17][18][19] It is possible that the concentration of zaprinast used in this study was too low to achieve a meaningful effect.…”
Section: Discussionmentioning
confidence: 97%
“…The medication was dosed based on previous work that suggested that beneficial effects on regional blood flow and cyclic mononucleotide levels without a significant reduction in mean arterial pressure could be achieved at 10 to 20 mg/kg doses. [17][18][19] It is possible that the concentration of zaprinast used in this study was too low to achieve a meaningful effect.…”
Section: Discussionmentioning
confidence: 97%